Neglected Duty: Providing Comprehensive Reparations to the Indonesian "1965 Victims" of State Persecution - Birks, Teresa (ICTJ, 2006)
As part of the International Centre for Transitional Justice's work in Indonesia, this monograph provides a contextual review of national and international instruments providing comprehensive reparations to victims of state persecution in Indonesia. This paper provides a background to the state persecution of alleged Indonesian Communist Party (PKI) members, sympathsiers and their families, legal instruments and practices used to legitimate persecution, civil society initiatives seeking justice for the victims, actions taken by successive governments since the fall of president Soeharto and critique of the truth commission legislation. The paper also includes a set of recommendations.